Effect of taking fodder crop on maize grain yield and soil chemical properties in Leucaena and Gliricidia alley farming systems in western Nigeria - Larbi, Asamoah; Jabbar, M.A.; Atta-Krah, A.N.; Cobbina, J. (Cambridge University Press, 1993)
The effect of managing hedgerow foliage for mulch and fodder in Leucaena leucocephala and Gliricidia sepium alley farming systems on maize grain yield and soil chemical characteristics was studied in on-station and on-farm experiments in southwestern Nigeria. Yields increased as the proportion of mulch applied increased but the extra increases obtained when more than half the foliage was applied as mulch were relatively small, suggesting that half the foliage may be removed as feed without deterimental effect. Soil organic carbon, nitrogen and available phosphorus tended to increase with increasing proportion of prunings applied as mulch.